Bài 4: Thực hiện phép tính
(x+3y)(y-2x2) - (2x+3)4 : (4x2+12x+9)
Bài 5: Thu gọn biểu thức
a) (32+1)(34+1)(38+1)(316+1)
b) (7x+6)2 + (5-6x)2 - (10-12x)(7x+6)
Bài 6: Tìm x biết
a) (4x-7)(x-3) - (7-4x)2 = 0
b) (2x+1)5 = 8x3 +12x2+6x+1
c) x3-x2+x = 1
Bài 7: Tính giá trị biểu thức
a) x2 - 2y2 - xy - x + 2y biết x+y=1
b) \(\frac{^{x^3}}{8}-\frac{9x^2}{4}+\frac{27x}{2}-27\) biết x=106
Bài 8: Tìm a,b,c biết
2(a2+b2+ab-b-ac)+(c2+1) = 0
6) c) x3 - x2 + x = 1
<=> x3 - x2 + x - 1 = 0
<=> (x3 - x2) + (x - 1) = 0
<=> x2 (x - 1) + (x - 1) = 0
<=> (x - 1) (x2 + 1) = 0
=> x - 1 = 0 hoặc x2 + 1 = 0
* x - 1 = 0 => x = 1
* x2 + 1 = 0 => x2 = -1 => x = -1
Vậy x = 1 hoặc x = -1
Bài 5:
a) Đặt \(A=\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^8-1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^{16}-1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=3^{32}-1\)
\(\Rightarrow A=\frac{3^{32}-1}{8}\)
b) (7x+6)2 + (5-6x)2 - (10-12x)(7x+6)
=(7x+6)2 + (5-6x)2 - 2(5-6x)(7x+6)
\(=\left(7x+6-5+6x\right)^2\)
\(=\left(13x+1\right)^2\)